Creativity in motion: examining the impact of meaningful movement on creative cognition - Frith, Emily; Miller, Stephanie E. (Frontiers in Cognition, 2024)
This study examined the link between creative cognition and meaningful physical movement among university students (N = 151) from a cognitive offloading perspective. A linear mixed model, repeated measures design examined whether divergent thinking on three Alternative Uses Tasks (AUTs; within-subjects factor) was influenced by movement in three independent experimental groups: 1) gesture as meaningful movement (n = 51), 2) meaningless movement (n = 50), and 3) restricted movement, (n = 50). Linear mixed model results indicated that changes in AUT fluency, flexibility, and originality across trials did not significantly interact with group. However, baseline gesture frequency was positively associated with all four creativity outcome measures and moderated group-level changes in originality across trials. Infrequent baseline gesturers demonstrated lower originality scores in the gesture as meaningful movement group compared to those in the restricted movement group. More frequent baseline gesturers experienced higher originality in both the gesture as meaningful movement and meaningless movement groups compared to those in the restricted movement group. This study demonstrates that the cognitive processes involved in novel idea generation may be differentially impacted by movement and may be more sensitive to individual differences in movement predisposition than experimental movement manipulation.